DILEMA PERAN GURU DALAM MENEGAKKAN DISIPLIN SISWA PADA ERA UNDANG-UNDANG PERLINDUNGAN ANAK - Nisa’ Atus Sholihah; Syaikhu Rozi; Muhammad Ali Rohmad (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Abstract Although the enforcement of student discipline within the framework of child protection regulations has received increasing attention in prior studies, research specifically addressing the role conflict and pedagogical dilemmas of teachers in state secondary schools under Child Protection Law No. 35 of 2014 remains limited. This study aims to analyze the objective reality of student discipline, identify the forms of role dilemmas faced by teachers, and examine teachers' strategies in managing these challenges at SMP Negeri 1 Mojoanyar. A qualitative approach was employed using a case study design, involving school administrators, homeroom teachers, Islamic religious education teachers, and students as informants selected through purposive sampling. Data were collected using semi-structured interviews, participatory observation, and documentation studies, and analyzed using interactive thematic analysis including data condensation, data display, and conclusion drawing, with validity tested through source and method triangulation. The findings indicate that student discipline is polarized into minor violations (such as tardiness and uniform infractions) and serious violations disrupting the teaching-learning process (such as verbal bullying and truancy). Furthermore, teachers experience role ambivalence and neurotic anxiety regarding potential criminalization, leading to defensive teaching practices. To overcome this, a Humanistic-Dialogic Discipline Management Model was reconstructed, integrating learning contracts, restorative personal communication, role modeling (uswah hasanah), substitutive academic-educative sanctions, and progressive tripartite collaboration among teachers, guidance counselors, and parents. These results contribute to the theoretical development of educational management and expand the understanding of teacher professionalism under legal protection frameworks. The study concludes that balancing pedagogical authority and child protection requires collaborative restorative approaches, and recommends that educational institutions and policymakers establish clear operational guidelines and legal protection mechanisms for educators.